Comparative Genomics of Pediococcus pentosaceus Isolated From Different Niches Reveals Genetic Diversity in Carbohydrate Metabolism and Immune System - Jiang, Jie; Yang, Bo; Ross, R. Paul; Stanton, Catherine; Zhao, Jianxin; Zhang, Hao; Chen, Wei (Frontiers in Microbiology, 2020)
Pediococcus pentosaceus isolated from fermented food and animal gastrointestinal tract have been widely identified, and some strains have been reported to reduce inflammation, encephalopathy, obesity and fatty liver in animals. In this study, 65 P. pentosaceus strains isolated from human feces, animal feces and different fermented food were genomic sequenced and compared them to the public genomes. The results revealed that this species shared the core genes encoding proteins related to translation, ribosomal structure and biogenesis and signal transduction mechanism, while the genetic diversity related mainly to carbohydrate metabolism, and horizontally transferred DNA, especially bacteriocin encoded by plasmid and prophage. Additionally, type IIA CRISPR/Cas system was firstly found in P. pentosaceus. This work provided expanded resources of P. pentosaceus genomes, and provided a framework for understanding the biotechnological potential of this species.